If Mass Digitization Is the Problem, Is Legislation the Solution? Some Practical Considerations Related to Copyright - Wasoff, Lois F. (The Columbia Journal of Law & the Arts, 2011)
Copyright law is intended to be “technology neutral.” Despite that, technological development is clearly putting pressure on certain aspects of copyright. Readily available technological tools make digital copying and distribution simple and seamless. This can make the legal “obstacles” to the full use of those tools resulting from the need to comply with copyright seem inconvenient and archaic. In particular, the issues arising in connection with mass digitization projects, where compliance can require identifying and locating large numbers of copyright owners and seeking appropriate permissions, are complicated. We hear often about the potential benefits that could be derived from mass digitization projects; we hear less often about some of the risks they may create. But the widespread interest in facilitating such projects, at least for certain purposes, is clear. Collective licensing schemes may be one way to accomplish that; targeted exceptions to copyright may be another. Either may require making changes to current copyright law.